SEM and AFM Studies of Two-Phase Magnetic Alkali Borosilicate Glasses - N. Andreeva; M. Tomkovich; A. Naberezhnov; B. Nacke; A. Filimonov; O. Alekseeva; P. Vanina; V. Nizhankovskii (The Scientific World Journal)
The morphology and composition of four types of two-phase alkali borosilicate glasses with magnetic atoms prepared by inductive melting have been studied. The results of scanning electron microscopy point to uniform distribution of Na, Si, and O atoms in these samples while magnetic iron atoms form ball-shaped agglomerates. The magnetic properties of these agglomerates have been confirmed by magnetic force microscopy. Atomic force microscopy had shown that in these samples two different morphological structures, drop-like and dendrite net, are formed. The formation of dendrite-like structure is a necessary condition for production of porous magnetic glasses. The obtained results allow us to optimize the melting and heat treatment processes leading to production of porous alkali borosilicate glasses with magnetic properties. The first results for nanocomposite materials on the basis of magnetic glasses containing the embedded ferroelectrics KH2PO4 demonstrate the effect of applied magnetic field on the ferroelectric phase transition.